Jóvenes y violencia en el ámbito escolar : Un análisis de las representaciones desde la prensa argentina (1993 - 2011). (2017)
This article presents the results of a research that analyzes the representation of young students in the mediatization of the phenomenon of violence in schools in the city of La Plata, Argentina, from 1993-2011. Given the characteristics of the study object, the methodological approach was qualitative and the information analysis stage was carried out within the framework of the socio-educational analysis of the discourse. Among the results obtained, we observe that in the forms of designating the "violent student" two dimensions are presented to characterize the young: the pathological and the cognitive-academic. Given the originality of the study, it provides a background for future research that addresses the association of young people with violence in the school space.